Specyfika kształcenia w zakresie muzykoterapii = Educational Benefits within the Field of Music Therapy - Colonna-Kasjan, Daniela (Kraków ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
The article presents matters related to education with the field of music therapy. When it comes to the educational functions, music therapy plays an important role when it comes to developing not only musical competence but also social competence, the level of general knowledge and level of experience related to communig with cultural knowledge and awareness.
Keywords: proces kształcenia; muzykoterapia; umiejętności muzyczne; kompetencje społeczne; educational process; music therapy; musical skills; social competences